1997
DOI: 10.1109/3.644114
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics of nonradiative defects in the bulk and surface of Brewster-cut Ti:sapphire laser materials using photothermal radiometry

Abstract: The understanding of the problem of nonradiative energy conversion in solid-state laser materials is a key factor in improving the overall efficiency of solid-state lasers. Furthermore, the reduction of the heat generated in an optically pumped laser crystal can lead to several new applications of solid-state lasers, especially in the high-power region. To improve the quality of grown crystals, laser crystal growers require accurate techniques to perform the quality control that is so vital to improving the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Furthermore, the almost identical values of Q s for the two crystals of different bulk quality confirm that early-time PTR detection is entirely insensitive to any bulk differences and can be used to monitor the optical quality of Ti:sapphire crystal surfaces through their efficiency as nonradiative power-conversion sites. These conclusions complement earlier results, 12 which showed that PTR can also Fig. 7.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, the almost identical values of Q s for the two crystals of different bulk quality confirm that early-time PTR detection is entirely insensitive to any bulk differences and can be used to monitor the optical quality of Ti:sapphire crystal surfaces through their efficiency as nonradiative power-conversion sites. These conclusions complement earlier results, 12 which showed that PTR can also Fig. 7.…”
Section: Discussionsupporting
confidence: 92%
“…It is therefore possible that any IR radiation in the 2-6-m range generated in the sample might not be reabsorbed by the sample and would therefore be collected by the detector. Comparison of the experimental data and theoretical predictions lead to the conclusion 10,12 that region II is due to surface-heating effects, and region III is due to bulk-heating effects, leaving region I as the region in which the source of the signal was as yet unaccounted for.…”
Section: B Identification Of Three Regimes Of Thermal Emissionmentioning
confidence: 96%
See 1 more Smart Citation
“…For further discussion, we do not exclude other fluorescence quenching possibilities such as X-ray induced defects which may cause non-radiative transitions. [49][50][51] Therefore, both X-ray-induced (Eu 2þ ) þ and defects are possible reasons for the fluorescence quenching of 420 nm emission. The former can reduce the effective Eu 2þ concentration by changing Eu 2þ to (Eu 2þ ) þ while the latter can induce non-radiative procedures, they both can quench the 420 nm defect emission.…”
Section: Discussionmentioning
confidence: 99%
“…Photothermal ͑PT͒ and photoacoustic ͑PA͒ spectroscopic techniques have been used successfully in measurements of optical absorption coefficients and nonradiative quantum efficiencies for a variety of optical materials, including laser crystals. [1][2][3][4][5][6][7][8][9][10][11][12][13] Among the various embodiments of PA and PT techniques, photopyroelectric detection ͑PPE͒, as pointed out elsewhere, [1][2][3][4][10][11][12]14 has a certain number of advantages. A major advantage of PPE detection over other conventional PT techniques is the fact that one can measure directly and self-consistently both the optical absorption coefficient, ␤͑͒, and the nonradiative quantum efficiency, ͑͒.…”
Section: Introductionmentioning
confidence: 99%